Pengembangan Aplikasi Multiplatform untuk Model Sistem Kendali dan Akuisisi Data Berbasis PC - Arief Hendra Saptadi (JUITA : Jurnal Informatika, 2015)
PC-based control and data acquisition system had enabled two-way communication between computer and data acquisition (DAQ) device. Application running on a PC serves to receive data from DAQ device and to deliver command to it. Despite of that, this application in general runs only on a particular operating system with an interface that utilizes  existing graphical shapes. The purpose of this research is to develop multiplatform application for a model of PC-based control and data acquisition system with self-designed graphical shapes.  All graphical objects and main program were developed with Processing programming language. Application interface was composed of simple graphical objects through several separate routines. Based on tests conducted in Windows and Linux, data acquisition device had been able to transmit data via serial communication to the PC. All modules on the application had run well. The appearance of application had been succesfully developed as it was previously designed. Functionality test had shown that all functions in the program were able to be operated. Overall, the application had operated well in Windows and Linux environment. To create graphical objects with more structured approach, all written routines can be enclosed in a separate library file. In future development, data communication between data acquisition device and PC can utilize handshake process